2017
DOI: 10.1002/ijc.31216
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor‐infiltrating Ly6G+ myeloid cells improves sorafenib efficacy in mouse orthotopic hepatocellular carcinoma

Abstract: Sorafenib, a multikinase inhibitor with antiangiogenic activity, is an approved therapy for hepatocellular carcinoma (HCC). It is unclear whether the proinflammatory and immunosuppressive mechanisms may limit the therapeutic efficacy of sorafenib in HCC. We used a syngeneic mouse liver cancer cell line to establish orthotopic liver or subcutaneous tumors to study how proinflammatory and immunosuppressive mechanisms impact on the efficacy of sorafenib. We found sorafenib exhibited a potent therapeutic effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Our current study suggested that macrophages, probably M2 type, were the dominant ICs expressing PD-L1 in the TME of advanced HCC after progression on sorafenib treatment. In our recently published paper employing a syngeneic mouse HCC model in immunocompetent mice, we found the liver tumors exhibited an increase in multiple cytokines, including transforming growth factor-β, TNF-α, IL-10, and interferon-γ, after sorafenib treatment [25]. Whether these cytokines induce adaptive immunity and increase PD-L1 expression in surrounding ICs, such as macrophages, needs further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…Our current study suggested that macrophages, probably M2 type, were the dominant ICs expressing PD-L1 in the TME of advanced HCC after progression on sorafenib treatment. In our recently published paper employing a syngeneic mouse HCC model in immunocompetent mice, we found the liver tumors exhibited an increase in multiple cytokines, including transforming growth factor-β, TNF-α, IL-10, and interferon-γ, after sorafenib treatment [25]. Whether these cytokines induce adaptive immunity and increase PD-L1 expression in surrounding ICs, such as macrophages, needs further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…In vivo and in vitro studies demonstrated that sorafenib may enhance antitumour immunity by increasing the M1 polarisation of TAMs, [86][87][88] enhancing CD4+ and CD8+ T cell infiltration and function, [89][90][91] suppressing Treg numbers, [91][92][93][94] or reversing the function MDSCs in the tumour microenvironment. 88,95,96 Other MKIs (lenvatinib, regorafenib, and cabozantinib) have also demonstrated antitumor immune activity in various pre-clinical models. 78,79,81,97 While many of the immunomodulatory effects may be linked to the VEGFR-inhibitory property of these MKIs, multiple cellular and soluble factors in the tumour microenvironment may mediate their immunomodulatory effects (Fig.…”
Section: The Importance Of Predictive Biomarkersmentioning
confidence: 99%
“…The effects of sorafenib may be dose-dependent: lower dosage is more likely to induce vascular normalisation, reduce hypoxia, and improve antitumor immunity (beneficial effects). By contrast, higher dosage may paradoxically enhance hypoxia and promote immune suppression (detrimental effects)(96). The dosage effects of other multikinase inhibitors (regorafenib, lenvatinib, and cabozantinib) warrant further investigation.…”
mentioning
confidence: 99%
“…By contrast, in HCC mouse models or studies using peripheral blood mononuclear cells (PBMCs), the number and function of CD4þ and CD8þ T cells may be depressed directly by sorafenib or indirectly by elevation of MDSCs and Tregs after sorafenib treatment. 76,77 Lenvatinib was shown to enhance recruitment of memory T cells and IFN-γ-producing CD8 T-cell populations thus may have potential synergistic effect with anti-PD1 therapy. 67,68 Regulatory T cells (Tregs).…”
Section: Immune Modulatory Effects Of Targeted Therapy For Hcc: a Sysmentioning
confidence: 99%
“…In HCC mouse models, either high-or low-dose sorafenib treatment has been reported to increase or decrease MDSCs, leading to contradictory effect on the immune microenvironment. 47,53,76,78,85,86 The increase of MDSCs may be associated with hypoxia and SDF-1α/CXCR4 pathway and further inhibit CD4 and CD8 T cell activity. However, Farsaci et al suggested that MDSCs recruited by sorafenib treatment may undergo a switch of immunesuppressive to an immune-active phenotype, characterized by increased activation markers: FAS-L, CXCL-9, CD31, and CD105.…”
Section: Immune Modulatory Effects Of Targeted Therapy For Hcc: a Sysmentioning
confidence: 99%